2022
DOI: 10.1002/ps.7315
|View full text |Cite
|
Sign up to set email alerts
|

Importance of adjuvant formulation properties in predicting wetting on leaf surfaces

Abstract: BACKGROUNDLeaf wettability can be a barrier to retention of agrichemical sprays. Adjuvants are used to modify leaf wetting by sprays to enhance retention. A previous study developed a model that accurately predicted nonadjuvant formulation wetting (contact angle) on both synthetic and leaf surfaces. Model inputs were the surface properties, roughness and polarity, as measured by the wetting tension dielectric method, coupled with the formulation properties, surface tension and dielectric constant. Preliminary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
(123 reference statements)
0
3
0
Order By: Relevance
“…117 As such, leaf surface wettability is of utmost importance as it is the preceding step to the leaf adhesion of the respective droplets, as well as their spreading, and retention on the leaf. 118 The tomato leaf, used as a model in this work, presents a characteristic high water contact angle of 118 ± 4° which prevents its wetting (see Fig. 4E).…”
Section: Resultsmentioning
confidence: 95%
“…117 As such, leaf surface wettability is of utmost importance as it is the preceding step to the leaf adhesion of the respective droplets, as well as their spreading, and retention on the leaf. 118 The tomato leaf, used as a model in this work, presents a characteristic high water contact angle of 118 ± 4° which prevents its wetting (see Fig. 4E).…”
Section: Resultsmentioning
confidence: 95%
“…33 Research indicates that vegetable oil, polymers, and non-ionic surfactants significantly boost spray deposition and anti-drift performance. [34][35][36] Most existing studies focus on adjuvant with single component, with limited research on combined adjuvant with multiple chemical components and the effect of downwash airflow on spraying. Comprehensive research on the influence of adjuvants on the physicochemical properties of the liquid, spraying characteristics, spray drift, canopy spray deposition, and control efficacy in UAV applications remains scarce.…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that the properties of the leaf surface were more important than the formulations. In a follow‐up paper Nairn & Forster 3 studied the wetting of a range of adjuvant formulations and found that the previously developed wetting model was also able to predict the wetting of adjuvant formulations ( R 2 = 0.90) using a novel method to quantify the interfacial dielectric polarity, one of the input parameters required to run the model. It is expected that the wetting model will allow, for example, formulation chemists to better select adjuvants to obtain formulations with the desired wetting outcomes.…”
mentioning
confidence: 99%